That would be
cos x
sin x + cos x * --------
sin x
sin x
Mult sin x by ----------
sin x
to obtain
(sin x)^2
------------
sin x
and then add
(cos x)^2
-------------
sin x
with the outcome being
(sin x)^2 + (cos x)^2 1
--------------------------- = --------- = cos x (answer)
sin x sin x
Answer:
x = (2 i π n)/log(4) + log(2 sqrt(2))/log(4) for n element Z
Step-by-step explanation:
Solve for x:
2 sqrt(2) = 4^x
Hint: | Reverse the equality in 2 sqrt(2) = 4^x in order to isolate x to the left hand side.
2 sqrt(2) = 4^x is equivalent to 4^x = 2 sqrt(2):
4^x = 2 sqrt(2)
Hint: | Eliminate the exponential from the left hand side.
Take the logarithm base 4 of both sides:
Answer:x = (2 i π n)/log(4) + log(2 sqrt(2))/log(4) for n element Z
Let use h= hotdogs price and c=chips price
we know that
4h +4c= 17
5h+3c=17.75
t use the elimination method we will multiply the first equation by 5 and the second one by (-4)
20h +20c=85
-20h -12c= -71
8c=14, we will divide by 8 both side and c=1.75, so a bag of potato chips cost $ 1.75
now we will substitute the c in the first equation
4h+7=17 therefore 4h=17-7, 4h=10, h=2.50
a bag of potato chips is 1.75
a hot dog costs 2.50
Answer:
i believe its the second one.
Step-by-step explanation:
the second line plot is the one that seems most right to me
Answer:
The next one is 64. Can you mark branliest if it's right?